Improving Elementary Students’ Speaking Skills through Contextual Learning and Folktale-Based Role Play - Indri Rahmawati (Pusat Unggulan Ipteks Javanologi Universitas Sebelas Maret, 2025)
This study was motivated by the low speaking skills of elementary school students, particularly in terms of expression and confidence. The purpose of this study was to determine the effectiveness of the Contextual Learning Model combined with role play based on folk tales in improving the speaking skills of students at Mojo 58 Sragen Public Elementary School. This study used a One-Group Pretest-Posttest Design with 26 students (N = 26) as subjects. Data were obtained through speaking ability tests before and after the model was implemented, which were then analyzed using Normalized Gain to measure learning outcome improvement. The results of the analysis showed that the application of the Contextual Learning Model with the integration of videos and role-play provided a significant improvement in students' speaking skills, with a Normalized Gain score of 0.778, which is classified as high according to Hake's criteria. These findings indicate that speaking learning based on real contexts and role-playing activities is effective in building students' communication performance, especially in terms of expression, fluency, and confidence. Based on these results, it is recommended that teachers apply contextual and role-play approaches continuously in language learning activities to foster more natural and meaningful communication skills for elementary school students.